2017
DOI: 10.1111/gcbb.12489
|View full text |Cite
|
Sign up to set email alerts
|

Biochars from local agricultural waste residues contribute to soil quality and plant growth in a Cerrado region (Brazil) Arenosol

Abstract: Arenosols (sandy soils) in the Cerrado region of Mato Grosso, Brazil, are increasingly used for maize production, the second most important crop in the region after soybean. Yet, these soils are typically nutrient poor with low soil water retention, requiring high fertilizer inputs that are often lost in surface runoff or leached. The addition of biochar, a more recalcitrant organic amendment, may therefore be beneficial in Cerrado Arenosols, contributing to sustainable crop production in the region. To examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 36 publications
3
23
0
3
Order By: Relevance
“…In our study, the application of pyrolyzed materials did not increase maize yield compared to the control treatment. This might be due to their low N availability, since maize is known to be a crop with high N demand [68,69]. On the contrary, we observed an increase in plant growth-meaning the aerial part-of 60% for the Incubated mixture (Figure 1).…”
Section: Effects On Corn Productionmentioning
confidence: 70%
See 1 more Smart Citation
“…In our study, the application of pyrolyzed materials did not increase maize yield compared to the control treatment. This might be due to their low N availability, since maize is known to be a crop with high N demand [68,69]. On the contrary, we observed an increase in plant growth-meaning the aerial part-of 60% for the Incubated mixture (Figure 1).…”
Section: Effects On Corn Productionmentioning
confidence: 70%
“…Some studies did not find differences in Fe availability in soil after amendment with biochars from different wastes [72]. Whereas others, such as Speratti et al, (2017) [69], found that Fe availability doubled after the application of sugarcane filtercake biochar in a tropical arenosol.…”
Section: Effects On Corn Productionmentioning
confidence: 96%
“…These soils are known as acid soils. These soils contain high concentration of aluminum and manganese, being necessary the use of liming to increase crop production [1] [2].…”
Section: Introductionmentioning
confidence: 99%
“…The production areas are in a Cerrado region with soils that have low natural fertility and high soil acidity, the costs with correction and fertilization contribute to the increase in production expenditures. These soils contain a high concentration of aluminum and manganese, and it is necessary to perform the liming to increase the agricultural production (SANTOS et al, 2018;SPERATTI et al, 2018).…”
Section: Introductionmentioning
confidence: 99%